Penerapan Model Pembelajaran Kooperatif Tipe STAD dengan Pendekatan Kontekstual bagi Siswa SDN 7 Tentena Sulawesi Tengah - Sustin Sumarni Burengge (Jurnal Paedagogy, 2020)
The purpose of this study was to describe student activities, teacher activities, student learning outcomes and student responses during the application of the STAD type learning model with a contextual approach. This research method uses classroom action research. This research was conducted in class II SDN 7 Tentena which consisted of three cycles. The data collection techniques used were observation, tests and documentation. Meanwhile, the data analysis technique used in this research was qualitative and quantitative descriptive analysis. The results of this study indicate that students are active in the aspects of understanding problems, discussions, and working in groups, even with positive student responses to the learning that has been done, the management of the teaching and learning process is in a good category because all aspects are implemented and student learning outcomes can be achieved. So it can be concluded that the application of STAD type learning with a contextual approach can achieve student learning outcomes.